Progesterone and Bone: Actions Promoting Bone Health in Women - Vanadin Seifert-Klauss; Jerilynn C. Prior (Journal of Osteoporosis)
Estradiol (E2) and progesterone (P4) collaborate within bone remodelling on resorption (E2) and formation (P4). We integrate evidence that P4 may prevent and, with antiresorptives, treat women's osteoporosis. P4 stimulates osteoblast differentiation in vitro. Menarche (E2) and onset of ovulation (P4) both contribute to peak BMD. Meta-analysis of 5 studies confirms that regularly cycling premenopausal women lose bone mineral density (BMD) related to subclinical ovulatory disturbances (SODs). Cyclic progestin prevents bone loss in healthy premenopausal women with amenorrhea or SOD. BMD loss is more rapid in perimenopause than postmenopause—decreased bone formation due to P4 deficiency contributes. In 4 placebo-controlled RCTs, BMD loss is not prevented by P4 in postmenopausal women with increased bone turnover. However, 5 studies of E2-MPA co-therapy show greater BMD increases versus E2 alone. P4 fracture data are lacking. P4 prevents bone loss in pre- and possibly perimenopausal women; progesterone co-therapy with antiresorptives may increase bone formation and BMD.